Surface optical phonon-assisted exciton photoluminescence spectroscopy in Q1D AlN nanostructures - Zhang, Li; Liang, Z. W.; Liu, Q.; Yang, A. L.; Shi, Jun-Jie; Wang, Qi (Applied physics letters, 2023)
Mechanisms and influence factors of surface optical (SO) phonon-mode-assisted exciton photoluminescence (PL) spectroscopy in quasi-1-dimensional (Q1D) nitride nanostructures remain a subject of debate. In this work, using momentum and energy conservation laws, a constraint relationship for the frequency and wave number of SO phonon-mode-assisted exciton PL is established. Using the dispersion relationships of SO modes in anisotropic wurtzite nanowires, the frequency and wave number of SO-mode-assisted exciton PL emission are determined. The present theoretical scheme and numerical results not only explain a current experimental discrepancy but could also be used to predict and design exciton PL spectroscopy with SO phonon modes in Q1D nanostructures.